Mitochondrial Reactive Oxygen Species and Kidney Hypoxia in the Development of Diabetic Nephropathy - Schiffer, Tomas A.; Friederich-Persson, Malou (Frontiers in Physiology, 2017)
The underlying mechanisms in the development of diabetic nephropathy are currently unclear and likely consist of a series of dynamic events from the early to late stages of the disease. Diabetic nephropathy is currently without curative treatments and it is acknowledged that even the earliest clinical manifestation of nephropathy is preceded by an established morphological renal injury that is in turn preceded by functional and metabolic alterations. An early manifestation of the diabetic kidney is the development of kidney hypoxia that has been acknowledged as a common pathway to nephropathy. There have been reports of altered mitochondrial function in the diabetic kidney such as altered mitophagy, mitochondrial dynamics, uncoupling and cellular signaling through hypoxia inducible factors and AMP-kinase. These factors are also likely to be intertwined in a complex manner. In this review we discuss how these pathways are connected to mitochondrial production of reactive oxygen species (ROS) and how they may relate to the development of kidney hypoxia in diabetic nephropathy. From available literature, it is evident that early correction and/or prevention of mitochondrial dysfunction may be pivotal in the prevention and treatment of diabetic nephropathy.